2017
DOI: 10.5414/cn108957
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis is a reasonable option in patients with cardiovascular disease

Abstract: This study compared incident PD patients with and without CV disease. CV disease patients were older but clinical and laboratorial targets, peritonitis rates, hospitalizations, and technique survival were similar between both groups, suggesting PD as an effective therapy for patients with CV comorbidities.
.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In 3 patients the recurrency of this infection led to PD drop out and 4 patients had to change to EUF due to peritoneal ultrafiltration failure. Like others, our results showed good technique survival without a higher peritonitis rate [5,23,24].…”
Section: Discussionsupporting
confidence: 86%
“…In 3 patients the recurrency of this infection led to PD drop out and 4 patients had to change to EUF due to peritoneal ultrafiltration failure. Like others, our results showed good technique survival without a higher peritonitis rate [5,23,24].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, long‐term follow‐up of 1375 patients with normal LV systolic function showed that a baseline LAVi above ≥32 mL/m 2 is an independent predictor for the development of congestive heart failure. It has been also demonstrated to have a better predictive value in the prediction of postoperative AF development as compared to left ventricular global strain and ejection fraction …”
Section: Discussionmentioning
confidence: 99%
“…It has been also demonstrated to have a better predictive value in the prediction of postoperative AF development as compared to left ventricular global strain and ejection fraction. 6,[13][14][15][16][17] There are several studies reporting the increase of left atrial volume to be a mortality predictor in dialysis patients. 7 Tripelli found a significant association between LAVi and cardiovascular event and indicated that association to be independent of basal left atrial and ventricular mass.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Atherosclerosis contributes to a significant increase in CVD and mortality in patients on peritoneal dialysis (PD), the most common causes being myocardial infarction, cardiac failure, stroke, and sudden cardiac death. [ 10 11 ] The increased CV burden in CKD may be mediated by mechanisms other than atherosclerosis, such as arterial media calcification or stiffening. [ 12 ] Changes in the vascular system in uremic patients are attributed to the synergistic action of numerous factors, such as prothrombotic factors, dyslipidemia, anemia, hypertension, increased oxidative stress, disruption of the synthesis of parathormone (PTH), homocysteine, and nitric oxide, abnormalities of endothelial function, which leads to remodeling of the vascular system.…”
Section: Introductionmentioning
confidence: 99%